Answer:
(g+f)(x)=(2^x+x-3)^(1/2)
Step-by-step explanation:
Given
f(x)= 2^(x/2)
And
g(x)= √(x-3)
We have to find (g+f)(x)
In order to find (g+f)(x), both the functions are added and simplified.
So,
(g+f)(x)= √(x-3)+2^(x/2)
The power x/2 can be written as a product of x*(1/2)
(g+f)(x)= √(x-3)+(2)^(1/2*x)
We also know that square root dissolves into power ½
(g+f)(x)=(x-3)^(1/2)+(2)^(1/2*x)
We can see that power ½ is common in both functions so taking it out
(g+f)(x)=(x-3+2^x)^(1/2)
Arranging the terms
(g+f)(x)=(2^x+x-3)^(1/2) ..
Answer:
x = 2
Step-by-step explanation:
Used a scientific calculator.
Answer: A rectangles angles are always equal.
Step-by-step explanation:
Suppose you have a rectangle, four sides, two pairs of parallel lines. in order to be a rectangle, the quadrilateral has to have equal angles, similar to a square, if they didn't, they could be a trapezoid, which is not a rectangle, because it only has one pair of parallel lines.
Hope this helps!
Answer:
<h2>4</h2>
Step-by-step explanation:
<em>Look at the picture.</em>
<em />
<em>At the beginning we have to calculate what part of the angle 360° is the given angle 75°.</em>
<em />
<em />
<em>The same part of the circumference of the circle is the arc defined by this central angle.</em>
The circumference <em>C = 20</em>.
Therefore
![x=0.2\cdot20=4](https://tex.z-dn.net/?f=x%3D0.2%5Ccdot20%3D4)
Answer:
x - 5
Step-by-step explanation: